Civility and its development : the experiences of China and Taiwan - Schak, David C. (The Hong Kong University Press, 2018)
This is the first book-length study of the development of civility in Chinese societies. Although some social scientists and political philosophers have discussed civility, none has defined it as an analytical tool to systematically measure attitudes and behavior, and few have applied it to a non-Western society. By comparing the development of civility in mainland China and Taiwan, Civility and Its Development: The Experiences of China and Taiwan analyzes the social conditions needed for civility to become established in a society. Schak argues that the attempts to impose civility top-down fr.